International business - Les R. Dlabay (South-Western Cengage Learning, 2001)
International Business 2E provides the foundation for studying international business and the many aspects of conducting business in the global economy. After studying International Business 2E, students should develop the appreciation, knowledge, skills, and abilities needed to live and work in a global marketplace. New to this edition, the Annotated Instructor's Edition brings together a wealth of teaching tips and marginal notes in one convenient book. This is a new edition of Business in a Global Economy